“Peran UMKM Cemilan Boga Rasa dalam Membangun Pertumbuhan Ekonomi di Kecamatan Mangli, Kabupaten Jember” - Fierena Riza Guntari; Fauziyah Almas Janani Widodo; Muhammad Rizky Al Zam Zami (Jurnal Strategi Bisnis Teknologi, 2024)
Economics is an inseparable thing in human life, especially when it comes to human needs themselves. One aspect of the economy is related to the economic sectors involved. The home industry of flavored food snacks is one of the economic sectors, where this business aims to fulfill consumer tastes. This research uses a qualitative research method with a phenomenological approach because it is hoped that it will be able to examine in more detail individual experiences related to the business being run. Through this research, it is hoped that we will be able to describe the growth and development of economic businesses and the social networks involved in them. Through motivation that is in accordance with McClelland's motivation theory with the concept of the need for achievement, where efforts are made to achieve development, efforts are made that are based on personal achievement, not achievement.